Clinical features of renal injury in patients with HBV-related acute-on-chronic liver failure - ZHANG Qian; SHI Bao-xian; WU Liang (Linchuang shenzangbing zazhi)
Objective To explore the clinical features of renal injury in patients with HBV-related acute-on-chronic liver failure(ACLF). Methods The clinical data of 539 patients who were diagnosed as HBV-ACLF during the hospitalization were collected in Wuhan Tongji Hospital from October 2014 to May 2017. The features of renal injury were analyzed retrospectively. Results The renal injury occurred in 19.67%(106/539) patients with HBV-ACLF. The incidence was highest in ≥51-year-old group, 34.52%. Patients with infection, cirrhosis, long-time bed and diuretics were more susceptible to renal injury, with the ratio of 25.86%, 27.08%, 26.07% and 22.51% respectively. Albumin, total cholesterol, triglyceride, prothrombin activity, hemoglobin and platelet count were reduced in patients with renal injury, but the white blood cell count was increased as compared with those in patients without renal injury. Conclusions Renal injury is common in patients with HBV-ACLF, with a high incidence. The patients with older age, long-time bed, diuretics, infection and cirrhosis should be focused. Hypoalbuminemia, hypolipidemia, anemia, infection and coagulation abnormalities also should be treated immediately to avoid further aggravation of liver failure.